Surgical Explantation of Transcatheter Aortic Valve Bioprostheses: A Statewide Experience. (April 2021) - Brescia, Alexander A.; Deeb, G. Michael; Sang, Stephane Leung Wai; Tanaka, Daizo; Grossman, P. Michael; Sukul, Devraj; He, Chang; Theurer, Patricia F.; Clark, Melissa; Shannon, Francis L.; Chetcuti, Stanley J.; Fukuhara, Shinichi
Abstract : Background: Despite the rapid adoption of transcatheter aortic valve replacement (TAVR) since its initial approval in 2011, the frequency and outcomes of surgical explantation of TAVR devices (TAVR-explant) is poorly understood. Methods: Patients undergoing TAVR-explant between January 2012 and June 2020 at 33 hospitals in Michigan were identified in the Society of Thoracic Surgeons Database and linked to index TAVR data from the Transcatheter Valve Therapy Registry through a statewide quality collaborative. The primary outcome was operative mortality. Indications for TAVR-explant, contraindications to redo TAVR, operative data, and outcomes were collected from Society of Thoracic Surgeons and Transcatheter Valve Therapy databases. Baseline Society of Thoracic Surgeons Predicted Risk of Mortality was compared between index TAVR and TAVR-explant. Results: Twenty-four surgeons at 12 hospitals performed TAVR-explants in 46 patients (median age, 73). The frequency of TAVR-explant was 0.4%, and the number of explants increased annually. Median time to TAVR-explant was 139 days and among known device types explanted, most were self-expanding valves (29/41, 71%). Common indications for TAVR-explant were procedure-related failure (35%), paravalvular leak (28%), and need for other cardiac surgery (26%). Contraindications to redo TAVR included need for other cardiac surgery (28%), unsuitable noncoronary anatomy (13%), coronary obstruction (11%), and endocarditis (11%). Overall, 65% (30/46) of patients underwent concomitant procedures, including aortic repair/replacement in 33% (n=15), mitral surgery in 22% (n=10), and coronary artery bypass grafting in 16% (n=7). The median Society of Thoracic Surgeons Predicted Risk of Mortality was 4.2% at index TAVR and 9.3% at TAVR-explant ( P =0.001). Operative mortality was 20% (9/46) and 76% (35/46) of patients had in-hospital complications. Of patients alive at discharge, 37% (17/37) were discharged home and overall 3-month survival was 73±14%. Conclusions: TAVR-explant is rare but increasing, and its clinical impact is substantial. As the utilization of TAVR expands into younger and lower-risk patients, providers should consider the potential for future TAVR-explant during selection of an initial valve strategy. Abstract : Supplemental Digital Content is available in the text.